تقريب مقاصد القرآن العقدية من خلال قصة أيوب عليه السلام وأثره على تفسير ابن عاشور (دراسة تحليلية) : An Approach to the Maqāṣid of Creed in the Qur’an Through the Story of Prophet Ayyub and its Influence on Ibn ʿāshūr’s Tafsīr: An Analytical Study - Taufik Hidayat, Fatmah; Syahrul Rahman (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The topic of maqāṣid al-ʿaqīdah (the higher objectives of Islamic creed) is a central issue in Islamic theology and Qur’anic studies. The stories within the Qur’an play a vital role in reinforcing the foundations of belief, deepening the understanding of Qur'anic texts, and actualizing them in building sound faith among Muslims. These stories also function as tools of daʿwah and vehicles for delivering Qur’anic messages, offering advice, lessons, clarity, guidance, and wisdom. This study aims to approach the meanings of maqāṣid al-ʿaqīdah through Qur’anic stories, taking the story of Prophet Ayyub (peace be upon him) as a case study. The research employs an inductive-analytical methodology by collecting and examining Qur’anic verses related to Ayyub’s story and identifying the objectives of creed conveyed through his experiences and conditions. The analytical method is applied to explore the values and creedal objectives reflected in these verses. The study finds that the verses detailing the story of Prophet Ayyub convey profound Qur’anic objectives such as steadfastness in faith, contentment with divine decree, and complete reliance on Allah during severe trials. The story also highlights key theological themes such as servitude, lordship, monotheism, divine justice, as well as various levels of patience and gratitude. Furthermore, it presents essential lessons about life’s trials and tests, along with ethical and spiritual values that every believer should embody on their journey toward Allah.